The Effect of Age on Thymic Function - Palmer, Donald B. (Frontiers in Immunology, 2013)
Age-related regression of the thymus is associated with a decline in naïve T cell output. This is thought to contribute to the reduction in T cell diversity seen in older individuals and linked with increased susceptibility to infection, autoimmune disease and cancer. Thymic involution is one of the most dramatic and ubiquitous changes seen in the ageing immune system, but the mechanisms which underlying this process are poorly understood. However, a picture is emerging, implicating the involvement of both extrinsic and intrinsic factors. In this review we assess the role of the thymic microenvironment as a potential target that regulates thymic involution, question whether thymocyte development in the aged thymus is functionally impaired and explore the kinetics of thymic involution.